Haematological changes from conception to childbirth: An indicator of major pregnancy complications. (4th September 2022) - Patxot, Marion; Stojanov, Miloš; Ojavee, Sven Erik; Gobert, Rosanna Pescini; Kutalik, Zoltán; Gavillet, Mathilde; Baud, David; Robinson, Matthew R.
Abstract: Background: About 800 women die every day worldwide from pregnancy‐related complications, including excessive blood loss, infections and high‐blood pressure (World Health Organization, 2019). To improve screening for high‐risk pregnancies, we set out to identify patterns of maternal hematological changes associated with future pregnancy complications. Methods: Using mixed effects models, we established changes in 14 complete blood count (CBC) parameters for 1710 healthy pregnancies and compared them to measurements from 98 pregnancy‐induced hypertension, 106 gestational diabetes and 339 postpartum hemorrhage cases. Results: Results show interindividual variations, but good individual repeatability in CBC values during physiological pregnancies, allowing the identification of specific alterations in women with obstetric complications. For example, in women with uncomplicated pregnancies, haemoglobin count decreases of 0.12 g/L (95% CI −0.16, −0.09) significantly per gestation week ( p value <.001). Interestingly, this decrease is three times more pronounced in women who will develop pregnancy‐induced hypertension, with an additional decrease of 0.39 g/L (95% CI −0.51, −0.26). We also confirm that obstetric complications and white CBC predict the likelihood of giving birth earlier during pregnancy. Conclusion: We provide a comprehensive description of the associations between haematological changes through pregnancy and three major obstetric complications to support strategies for prevention, early‐diagnosis and maternal care.